Wind power integration connection and system operational aspects - Fox, Brendan; Flynn, Damian; Bryans, Leslie; Jenkins, Nicholas 1954-; Milborrow, David; O'Malley, M. (Mark); Watson, Richard (Wind power engineer); Anaya-Lara, Olimpo (Energy Engineering., 2007)
The rapid growth of wind generation has many implications for power system planning, operation and control. This would have been a considerable challenge for the old nationalised power companies; it has become an even greater challenge in today's liberalised electricity markets. Network development, voltage rise, protection, monitoring and control are connection problems common to all wind power generation. These issues are addressed through an understanding of the basic electrical engineering concepts and wind power technology. When wind power approaches 10 percent of all generation, it impinges on system operation. The underlying principles of system balancing are presented, before considering the impact of many variable generation sources whose outputs are difficult to predict. Wind power forecasting is crucial to successful wind power integration, and basic theory and current practice are considered. Storage can also help but it needs to be low cost and, ideally, based on intelligent use of existing load. Finally, electricity markets are explained and the commercial challenges facing wind power are assessed. The book provides a wide-ranging discussion on all major aspects of wind power integration into electricity supply systems. It requires no specialist knowledge and will appeal to engineers from various disciplines looking for an overview of a technology that is providing a major impetus for sustainable electricity supply in the twenty-first century.